2003
DOI: 10.1016/s0194-5998(03)00479-0
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between septal deviation and concha bullosa

Abstract: Septal deviation does not appear to give rise to the formation of CB, but augments the pneumatization of the middle turbinate depending on the degree of deviation angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
2
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 8 publications
3
49
2
9
Order By: Relevance
“…They observed that OMC obstruction in the direction of septal angulations was due to nasal septal deformity while contralateral OMC obstruction was related to middle turbinate and lateral wall abnormalities which appeared with increased frequency on the side opposite of septal deviation. 3 In the present study, it was observed that FESS with septoplasty is effective for the treatment of chronic rhinosinusitis with deviated nasal septum on VAS as well as radiologically (The Lund and Mackay Staging system: Radiologic Staging) than FESS alone. However statistical difference in two groups was found significant only in nasal blockage and overall discomfort on VAS and chronic maxillary sinusitis on HRCT Nose and PNS (p value ‹0.05).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…They observed that OMC obstruction in the direction of septal angulations was due to nasal septal deformity while contralateral OMC obstruction was related to middle turbinate and lateral wall abnormalities which appeared with increased frequency on the side opposite of septal deviation. 3 In the present study, it was observed that FESS with septoplasty is effective for the treatment of chronic rhinosinusitis with deviated nasal septum on VAS as well as radiologically (The Lund and Mackay Staging system: Radiologic Staging) than FESS alone. However statistical difference in two groups was found significant only in nasal blockage and overall discomfort on VAS and chronic maxillary sinusitis on HRCT Nose and PNS (p value ‹0.05).…”
mentioning
confidence: 51%
“…3 DNS leads to increased chance of impaired mucociliary clearance, ostiomeatal complex obstruction and development of rhinosinusitis. 4 Sinusitis is usually more severe on opposite side of deviated nasal septum.…”
mentioning
confidence: 99%
“…3 Uygur et al found this figure as 55.3%, 33.9% and 10.8% respectively. 10 Unlu et al found 45% lamellar type CB, 21% bulbous type CB and 34% extensive type CB. 11 In contrast to these studies, a different frequency of the type of CB was observed by Hatipoqlu et al who found 20.86% lamellar type, 32.17% bulbous type and 46.95% extensive type CB.…”
Section: Discussionmentioning
confidence: 96%
“…Bunlar içerisinde konka bülloza, septum pnömatizasyonu, paradoks orta konka, Haller hücresi, Onodi hücresi, anterior klinoid proçes pnömatizasyonu, unsinat proçes pnömatizasyonu sayılabilir [1]. Bu varyasyonlar içerisinde en sık görüleni orta konkanın değişik derecelerdeki pnömatizasyonu olarak tanımlanan konka bülloza, nazal pasaj içerisinde lateral nazal duvarın önemli ve sık rastlana bir anatomik varyasyonudur [2]. Konka pnömatizasyonu genellikle orta konkada görülmekle birlikte daha az oranda üst ve alt konkalarda da rastlanabilmektedir.…”
Section: Introductionunclassified